2018
DOI: 10.1371/journal.pone.0204347
|View full text |Cite
|
Sign up to set email alerts
|

Molecular assays for antimalarial drug resistance surveillance: A target product profile

Abstract: Antimalarial drug resistance is a major constraint for malaria control and elimination efforts. Artemisinin-based combination therapy is now the mainstay for malaria treatment. However, delayed parasite clearance following treatment with artemisinin derivatives has now spread in the Greater Mekong Sub region and may emerge or spread to other malaria endemic regions. This spread is of great concern for malaria control programmes, as no alternatives to artemisinin-based combination therapies are expected to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 76 publications
(54 reference statements)
0
39
0
Order By: Relevance
“…Active surveillance of imported malaria cases is an important public health activity in the USA and the EU [27,28]: it plays a pivotal role in estimating the incidence in imported malaria cases, preventing malaria reintroduction, and providing chemoprophylaxis guidelines to travelers to malaria endemic regions. Historically, anti-malaria drug resistance genotyping was performed using traditional low throughput sequencing methodologies, such as Sanger sequencing [29]. However, currently, next-generation sequencing and accompanying standardized bioinformatics tools provide advanced and rapid protocols for monitoring molecular marker genes involved in P. falciparum drug resistance [24].…”
Section: Discussionmentioning
confidence: 99%
“…Active surveillance of imported malaria cases is an important public health activity in the USA and the EU [27,28]: it plays a pivotal role in estimating the incidence in imported malaria cases, preventing malaria reintroduction, and providing chemoprophylaxis guidelines to travelers to malaria endemic regions. Historically, anti-malaria drug resistance genotyping was performed using traditional low throughput sequencing methodologies, such as Sanger sequencing [29]. However, currently, next-generation sequencing and accompanying standardized bioinformatics tools provide advanced and rapid protocols for monitoring molecular marker genes involved in P. falciparum drug resistance [24].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic efficacy studies are often not feasible due to economic and practical constraints in many settings in Sub-Saharan Africa (SSA). It has been suggested that molecular surveillance of genetic polymorphisms associated with antimalarial resistance could complement therapeutic efficacy studies (4-15) because these can provide early warning signs of decreasing antimalarial efficacy (5). Molecular surveillance only requires sampling of P. falciparum infected blood, which in turn can be acquired from finger prick samples, as used for malaria rapid diagnostic tests (RDTs) (16, 17).…”
Section: Background (Word Count (Incl Conclusion): 3577)mentioning
confidence: 99%
“…However, the use of NGS could be centralized to very few sub-regional reference laboratories located in malaria endemic countries [36,83,84]. This requires a lot of effort to develop the capacity not only for sequencing but more importantly for data analysis, a critical part in the path for developing countries to get access to these techniques [85][86][87]. This should be a concerted effort not only from the malaria community but from the global health community, as other diseases such as tuberculosis (TB), human immunodeficiency virus (HIV), and other bacterial and viral infections may benefit as well from these centers of excellence [88].…”
Section: Discussionmentioning
confidence: 99%